2021
DOI: 10.1002/etc.5140
|View full text |Cite
|
Sign up to set email alerts
|

A Deep Dive into the Complex Chemical Mixture and Toxicity of Tire Wear Particle Leachate in Fathead Minnow

Abstract: The ecological impact of tire wear particles in aquatic ecosystems is a growing environmental concern. In this study, we combined toxicity testing, using fathead minnow (Pimephales promelas) embryos, with non-target high-resolution liquid This article is protected by copyright. All rights reserved. Accepted Articlechromatography Orbitrap mass spectrometry to characterize the toxicity and chemical mixture of organic chemicals associated with tire particle (TP) leachates. We assessed:(a) exposure to TP leachates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
33
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(37 citation statements)
references
References 56 publications
0
33
0
Order By: Relevance
“…Overall, the studies investigating the toxicity of tire particle leachates led to contrasting results. These could originate from the variability of the exposure conditions but may also suggests species-specific sensitivity 14,17,18,[21][22][23][24] . A recent study incriminated a 6PPD oxidation product, namely 2-((4-methylpentan-2-yl)amino)-5-(phenylamino)cyclohexa-2,5-diene-1,4-dione (6PPD-Q), as responsible for acute toxicity to Coho salmon (Oncorhynchus kisutch), threatening the local population of this fish species in urban creeks of Seattle (United States of America) 25,26 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall, the studies investigating the toxicity of tire particle leachates led to contrasting results. These could originate from the variability of the exposure conditions but may also suggests species-specific sensitivity 14,17,18,[21][22][23][24] . A recent study incriminated a 6PPD oxidation product, namely 2-((4-methylpentan-2-yl)amino)-5-(phenylamino)cyclohexa-2,5-diene-1,4-dione (6PPD-Q), as responsible for acute toxicity to Coho salmon (Oncorhynchus kisutch), threatening the local population of this fish species in urban creeks of Seattle (United States of America) 25,26 .…”
Section: Introductionmentioning
confidence: 99%
“…A recent study found microplastics, including tire particles, in the stomach content of several wild fish species, showing that fish can also ingest TRWP 31 . Studies investigating direct effects of TRWP remain scarce 21,32,33 which highlights the need to investigate the effects of the particles themselves in addition to the effects of leachates 34 . Indeed, several studies showed that the solubilization of polymer-bound chemicals was enhanced in fish gut fluids compared to water and could promote bioaccessibility of the chemicals for uptake into the circulatory system [35][36][37][38][39][40] .…”
Section: Introductionmentioning
confidence: 99%
“…Studies have begun to evaluate the components that make up a plastic additive mixture and their higher proportion of toxic effects were observed when dosed with 10-d leachate and unfiltered leachates. While the authors were able to determine that benzothiazoles and aryl-amines were correlated with toxic effects, there are many other chemicals that could be contributing to the overall toxicity (Chibwe et al 2021); thus, further validating the complexity of plastic additive mixtures. Often combined with non-target screening techniques, effect-directed analyses use toxicity assays to determine whether a certain sample exhibits a toxic effect.…”
Section: Longmentioning
confidence: 99%
“…potential toxicological effects (e.g., tire leachate,Tian et al 2021;Chibwe et al 2021;McIntyre et al 2021; Halsband et al 2020). For example,Chibwe et al (2021) aimed to characterize the toxicity and chemical mixture of organic chemicals affiliated with tire particle leachate(Chibwe et al 2021). Through various exposures of tire leachate to fathead minnow (Pimephales promelas),…”
mentioning
confidence: 99%
“…In this special section collection, you will find (1) innovative NTA approaches in rapid response and emergency situations, (Phillips et al, 2022), (2) the combination of passive samplers and NTA for environmental monitoring in surface waters, (Renaud et al, 2022), (3) identification of chemicals of concern from tire wear particles in an aquatic ecosystem, (Chibwe et al, 2022), (4) comparison of different methodologies in the identification and prioritization of contaminants in surface water, (Ng et al, 2022), (5) source-tracking of chemicals introduced by wastewater, (Troxell et al, 2022), and (6) application of NTA to chemical signatures in sewage sludge during the COVID-19 pandemic (Nason et al, 2022a(Nason et al, , 2022b.…”
Section: Introductionmentioning
confidence: 99%